Analysis and Study on the Quality of Life of Patients Undergoing Transcatheter Aortic Valve Replacement. (16th December 2021) - Wu, Guoliang; Zhu, Jiajun; Hu, Kaixuan; Cai, Huan; Li, Xiaomei; Yang, Yining
Abstract : Objective . Explore the factors affecting the QO of life after transcatheter aortic valve replacement (TAVR) and analyze and evaluate their surgical efficacy and postoperative survival status. Methods . Through correlation analysis and multiple regression analysis, we predict various clinical characteristics and postoperative quality and predict clinical changes in L postoperative quality. Results . The quality of life of patients with the disease has gradually improved and improved from 6 months after surgery. The differences in the three aspects of its physiological mechanism function, physiological function function, overall health, and vitality are statistically significant (p < 0.05 ). Conclusion . Compared with traditional open-thoracic aortic valve (AV) surgery, TAVR has the significant advantages of smaller surgical incision and less trauma to the patient, which has become one of the reasons why patients are willing to accept it.